Enhancing Social Skills in Early Childhood through Cooperative Learning: A Case Study - Ayu, Candra; Dameaty Hutagalung, Fonny; Savana, Cayla; Indahsari , Anita; Jannah, Miftakhul (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2025)
Background of the study: Social skills are essential in early childhood development, shaping how children interact, collaborate, and communicate with others. Cooperative learning has emerged as an effective instructional model to nurture these skills within early education settings. At TK Permata Hati, a cooperative learning approach has been implemented to address challenges related to low confidence and limited social interaction among children. The school seeks to create a supportive, inclusive environment that encourages participation and peer engagement. Aims and scope of paper: This study aims to examine the implementation of the cooperative learning model at TK Permata Hati and its role in enhancing the social skills of young learners. The focus is on how structured group activities, such as discussions and role-play, foster collaboration, sharing, and verbal communication among students. Methods: This study used a qualitative case study design, the research involved observation, semi-structured interviews, and document analysis. Participants included the school principal, teachers, and students from Group A and B. This approach provided a comprehensive understanding of teaching practices and children’s responses in the cooperative learning environment.. Results: Findings revealed that cooperative learning significantly improved children’s social abilities. Children became more willing to cooperate, take turns, and express themselves verbally. Previously reserved students showed increased confidence and engagement. Activities like role-playing enhanced both academic understanding and empathy. However, challenges such as varied developmental levels and time constraints were identified. Solutions included balanced group arrangements and the use of engaging learning media. Contribution: The study affirms cooperative learning as a valuable strategy in early childhood education. It supports children’s social and academic growth while emphasizing the need for adaptive teaching methods. The findings offer practical implications for educators in fostering inclusive and interactive classrooms that support holistic development.